AN ERRORS ANALYSIS OF LANGUAGE USING BY THE STUDENTS' IN SPEAKING ACTIVITIES AT MA'HAD OF STATE ISLAMIC INSTITUTE OF KERINCI - Oki Mitra; Ainil Khuryati; Ilal Musallin; Widad Binti Mat Zin (Thariqah Ilmiah: Jurnal ilmu-ilmu kependidikan & Bahasa Arab, 2022)
This thesis examines the analysis of students' competence in understanding conversation on the program "Sabah Al-Lughah" at Karanji State Islamic University Institute.  Speaking proficiency is the ability to articulate sounds or articulate words to express ideas in the form of thoughts, opinions, desires, or feelings to the speaking partner. In a broader sense. Speech is a system of signs that can be heard and seen that use a number of muscles and muscular tissues in the human body to convey thoughts in order to satisfy their needs. The purpose of this research is to find out, understand and describe the process of Sabah Al-Lugha activities in Karanji State Islamic University Institute. This type of research is a field research using a qualitative descriptive approach. The method used to collect data is through observation, interview and documentation methods. The data in this thesis was obtained from several sources such as instructors, university institute students directly with the author's notes. The topic of research in this dissertation is Mahasneri in understanding the Arabic conversation in Shabha activities. This thesis describes the process of carrying out language morning activities. تبحث هذه الرسالة في تحليل كفاءة الطلاب فى فهم المحادثة على برنامج "صباح اللغة" بمعهد الجامعة الإسلامية الحكومية كرنجي. إتقان التحدث هو القدرة على التعبير عن الأصوات أو الكلمات المفصلية للتعبير عن الأفكار في شكل أفكار أو آراء أو رغبات أو مشاعر للشريك المتحدث. بمعنى أوسع، التحدث عبارة عن نظام من العلامات التي يمكن سماعها ورؤيتها والتي تستخدم عددًا من العضلات والأنسجة العضلية في جسم الإنسان لنقل الأفكار من أجل تلبية احتياجاتهم. الغرض من هذا البحث هو معرفة وفهم ووصف عملية أنشطة صباح اللغة في معهد الجامعة الحكومية الإسلامية كرنجي. هذا النوع من البحث هو بحث ميداني باستخدام منهج وصفي نوعي. الطريقة المستخدمة في جمع البيانات هي من خلال طرق المراقبة والمقابلة والتوثيق. تم الحصول على البيانات في هذه الرسالة من عدة مصادر مثل المدربين، طلاب معهد الجامعة مباشرة مع ملاحظات المؤلف. موضوع البحث في هذه الأطروحة هو محاسنري في فهم المحادثة العربية في أنشطة الشباحة. تصف هذه الرسالة عملية تنفيذ أنشطة صباح اللغة.